2016
DOI: 10.1016/j.jdiacomp.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin 2–2 genotype and the risk of coronary artery disease in the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications study (DCCT/EDIC)

Abstract: Aims/hypothesis Haptoglobin (Hp) 2-2 genotype has been shown to increase coronary artery disease (CAD) risk in numerous type 2 diabetes studies but in only one type 1 diabetes cohort. We assessed the association of Hp 2-2 with incident CAD over 26 years of follow-up in 1,303 Caucasian participants of the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) study. Methods DCCT randomized volunteers with type 1 diabetes to intensive versus conventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…61 In the large T1DM DCCT/EDIC cohort with duration of follow-up median 26 years, a significant association of myocardial infarction was seen with Hp2-2 individuals in the secondary cohort (consisting of patients with duration of diabetes: 1–15 years with early minor complications, for example, retinopathy/microalbuminuria). 62 These data suggest that in individuals with advanced T1DM, the Hp2-2 genotypes confer a higher risk of cardiovascular complications. This is consistent with the pathophysiology that when the system is stressed as in prolonged hyperglycaemic situations the Hp2-2 genotype confers a higher risk due to deficient antioxidative or anti-inflammatory pathways.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…61 In the large T1DM DCCT/EDIC cohort with duration of follow-up median 26 years, a significant association of myocardial infarction was seen with Hp2-2 individuals in the secondary cohort (consisting of patients with duration of diabetes: 1–15 years with early minor complications, for example, retinopathy/microalbuminuria). 62 These data suggest that in individuals with advanced T1DM, the Hp2-2 genotypes confer a higher risk of cardiovascular complications. This is consistent with the pathophysiology that when the system is stressed as in prolonged hyperglycaemic situations the Hp2-2 genotype confers a higher risk due to deficient antioxidative or anti-inflammatory pathways.…”
Section: Introductionmentioning
confidence: 88%
“…We have summarized in Table 2 the human studies looking at association of Hp genotypes with complications in T1DM. 5872 Studies have been conducted in three large cohorts of T1DM in the United States: 1. Coronary Artery Calcification in T1DM (CACTI); 2. the Pittsburgh Epidemiology of Diabetes Complications (EDC) study, and 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of De Bacquer et al reported an increased risk of cardiovascular events in non-diabetic patients with the Hp 1-1 phenotype in the Belgian Interuniversity Research on Nutrition and Health (BIRNH) survey [ 241 ]. The relevance of the Hp genotype for the cardiovascular risk in patients suffering DMT1 remains elusive [ 242 ].…”
Section: Controversial Outcome Of Rcts—explanatory Approachesmentioning
confidence: 99%
“…Systemic metabolic dysfunctions, such as hyperglycaemia, insulin resistance and dyslipidaemia, give rise to an elevated risk of cardio-cerebrovascular diseases, including cerebral infarction, stroke, and heart attacks [3, 4]. The pathogenesis underlying macroangiopathy is complicated and yet not well clarified [58]. A group of studies was previously launched to explore the causality underlying the relationship of several novel biomarkers with macroangiopathy risk [911], and a causal relationship between serum haptoglobin (Hp) levels and macroangiopathy was observed in Chinese T2DM patients via Mendelian randomization analysis [12].…”
Section: Introductionmentioning
confidence: 99%